A Critical Analysis of Kushthaghna Dravyas Mentioned in Sushrutokta Gana with Commentators View on Controversial Drugs (International Journal of Ayurveda and Pharma Research, 2023)
Ayurveda is one of the oldest medical systems with a holistic approach to health and individualize medicine. All the skin diseases in Ayurveda have been discussed under the broad heading of Kushtha. The literal meaning of Kustha is “Kushnati tad vapuhu” which means the Roga which causes discoloration, disfiguration. Acharya Charaka, Sushruta, and Vaghbhata mentioned Kushthghna Dravyas (drugs acting on skin diseases) in their books respectively. Sushruta Samhita is one of prime compendium of Ayurveda where various categorization (Gana) of drugs acting according to different ailments is mentioned in Sutrasthana 38th chapter named Dravyasangrehniya-adhyaya. The objective of the present article is to study the drugs which are mentioned in the category of the drugs which acts on Kushtha (Kushthghna), with their chemical constituents, and pharmacological actions with special reference to Sushruta Samhita and other related books. Rasa-panchaka, botanical names with family, contraversial identification according to commentator’s views are also discussed for better understanding of Dravyas. The review concluded that herbs mentioned in Ayurveda (Sushrutokta Gana) are beneficial in skin diseases and cosmetics in one or another way and also this article will help Ayurvedic UG/PG students, PhD scholars and Ayurveda physicians in both academics and clinical aspect.